Two cases of bronchiolitis obliterans organizing pneumonia syndrome after postoperative irradiation for breast cancer - Abe, Shuichi; Fukuzaki, Koji; Inoue, Sumito; Kubota, Isao; Nishiwaki, Michiko; Shibata, Yoko (Technische Universität Dortmund, 2011)
We report two cases of bronchiolitis obliterans organizing pneumonia (BOOP) syndrome that developed after postoperative radiation therapy for breast cancer. In both patients, chest radiographs and computed tomography (CT) showed multiple consolidations outside the irradiation fields after several months of tangential radiation therapy. These patients were diagnosed as having radiation-associated BOOP syndrome, based on their clinical course and the findings on examination. After treatment with a systemic corticosteroid, radiographic consolidations and symptoms improved rapidly. In cases where consolidations appear outside the irradiated field, it is important to consider BOOP syndrome as a pulmonary complication of radiation therapy for breast cancer.
EXCLI Journal ; Vol. 10, 2011
Keywords: BOOP (bronchiolitis obliterans organizing pneumonia) syndrome; breast cancer; radiation therapy; 610